IMPLEMENTASI EXPERT ADVISOR UNTUK TRADING OTOMATIS FOREX MENGGUNAKAN INDIKATOR RSI DAN MA DENGAN METODE MARTINGALE DI PLATFORM METATRADER 4 - Adi Riswan; Dadang Iskandar Mulyana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Among the many digital businesses, forex trading is one of them. To trade forex, various types of software are used which are tools for traders, such as Metatrader 4. The core business of forex trading is to buy or sell consistently to trade forex, making a profit. In order to get the desired profit, it is important to adjust the forecast towards a growing market. Therefore, we need the right forex indicators to predict prices that are not wrong. However, traders who follow predictive indicators signals often fail to execute trades on time and therefore are unable to make consistent profits. The solution for traders to find timely trading opportunities based on indicators is to create an automated forex trading system or Expert Advisor. Expert Advisor (EA) is a program/system that has the ability to appear in the terminal on the instructions of a trader without direct involvement. All tasks that the Expert Advisor performs automatically. Expert Advisors can work automatically without the need to monitor price movements for 24 hours. EA is designed to analyze the market based on 2 indicators RSI (Relative Strength Index) and MA (Moving Average) as a reference for prices that will occur and also as a reference for trading using the martingale method.